Analisis dan Evaluasi Penerapan Sistem Informasi Smart Library AMIKOM Resource Centre dengan Metode Pieces Framework - Dwiyantoro, Dwiyantoro (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2019)
Technological developments are currently running so fast along with the times. The information system is one of the technological developments. With the existence of information system of course very give big influence to institute or institution good of profit and non profit like library. Of course, the system used has advantages and disadvantages that need to be done a renewal so that the system can work effectively and efficiently. For that we need an analysis of the level of effectiveness and efficiency of a system. One of the methods that can be used in analyzing the system is PIECES Fremwork where there are 6 related indicators about performance, information, control / scuritu, efficiency, service. This study uses quantitative descriptive approach, with data collection techniques using questionnaires and observations. The results of this study in the form of statements about the information system in carefully. With PICES method is expected to be able to provide an overview of the shortcomings of the system used so that later the system can be improved and developed towards a better direction again.